2010 8th International Pipeline Conference, Volume 4 2010
DOI: 10.1115/ipc2010-31169
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the Stress-Strain Curves for Line Pipe Steels

Abstract: To suppress the appearance of Lu¨ders strain and to decrease yield to tensile strength ratio in the L-direction (longitudinal direction), as well as the C-direction (circumferential direction), have been more important for strain-based design. In this study, conventional UOE and ERW pipes were examined in terms of tensile properties in both directions. In the case of UOE pipes, yield point was clearly observed on the stress-strain curve in the C-direction. However, stress-strain curves in the L-direction showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Nagai et al [3] reported that discontinuous yielding behaviors occur in the API X80 linepipe steels. In addition, the uniform elongation decreases and the strain hardening exponent increases after thermal aging.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nagai et al [3] reported that discontinuous yielding behaviors occur in the API X80 linepipe steels. In addition, the uniform elongation decreases and the strain hardening exponent increases after thermal aging.…”
Section: Discussionmentioning
confidence: 99%
“…A pre-strain of 2 pct was given on the large-scale tensile specimens to simulate the strain state of the piping process. [3] The tensile tests were performed on the large-scale tensile specimens at room temperature at a strain rate of 0.003 s À1 using an Instron machine (model; 5567, Instron, Canton, MA, USA) with a 100 kN capacity. Heat treatment at 473 K and 523 K (200°C and 250°C) for 5 minutes was performed on the pre-strained largescale tensile specimens to simulate the epoxy coating process.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations